2022
DOI: 10.1016/j.anndiagpath.2021.151875
|View full text |Cite
|
Sign up to set email alerts
|

Remote Pathology teaching under the COVID-19 pandemic: Medical students' perceptions

Abstract: Context The COVID-19 pandemic has forced traditional teaching to be re-structured and delivered online. Objective To analyse medical students' perceptions about the benefits and difficulties of the remote teaching of Pathology during the COVID-19 pandemic. Design A cross-sectional study was performed with an online survey applied to students from the third and fourth year of medical graduation, who attended the remote teaching of Pathology du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 14 publications
4
21
0
Order By: Relevance
“…Notably, evaluation scores were often improved, compared to the previous years when traditional on-site delivery had taken place [ 5 , 9 ]. Medical students regarded the remote delivery of classes as flexible and less time-consuming, while they appreciated that teaching materials (e.g., session recordings and virtual slides) were available to access anytime and from anywhere [ 4 , 10 ]. On this subject, a group reported creating a YouTube channel containing all the high-quality recordings from their pathology sessions, which was very much appreciated by their students [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Notably, evaluation scores were often improved, compared to the previous years when traditional on-site delivery had taken place [ 5 , 9 ]. Medical students regarded the remote delivery of classes as flexible and less time-consuming, while they appreciated that teaching materials (e.g., session recordings and virtual slides) were available to access anytime and from anywhere [ 4 , 10 ]. On this subject, a group reported creating a YouTube channel containing all the high-quality recordings from their pathology sessions, which was very much appreciated by their students [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, instructors also reported that virtual laboratory sessions were effective in a recent study [ 21 ]. Of interest, some students often found the online sessions more interactive, engaging, and better structured compared to the conventional ones, finding it easier to participate and ask questions [ 4 , 6 ]. A study by Rodrigues et al reported that, although both sexes were asking more questions during virtual classes, female students felt significantly more comfortable doing so than males (48.9 vs. 33%, p < 0.03) [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations